The Oxford Brain Health Centre: Embedding dementia research in clinical practice: Other innovative programs and practices. (7th December 2020) - O'Donoghue, M Clare; Raymont, Vanessa; Fossey, Jane; Semple, Juliet; Griffanti, Ludovica; Zokaei, Nahid; Nobre, Anna Christina; Martos, Lola; Mackay, Clare
Abstract: Introduction: The Oxford Brain Health Centre (BHC) is an ambitious and innovative joint clinical‐research service that aims to bring UK NHS memory services into the 21 st century by addressing gaps between clinical practice and research advances into dementia. This NIHR‐funded partnership between Oxford Health NHS Foundation Trust and the University of Oxford will be the first psychiatry‐led service of its kind, developing the model for a specialist service that can be adopted throughout the UK health service. Methods and Materials: The BHC will augment current NHS memory services by providing high‐quality assessments not routinely available in clinical service, e.g. MRI rather than CT brain scans, and developing novel diagnostic tools sensitive to earlier pathological changes. Enhanced information will be fed into clinical notes, improving the quality of information available to clinicians empowered to make more confident and accurate timely diagnoses. The BHC will increase opportunities for patients and relatives to participate in research by embedding research in the clinical service, through use of clinical data for research, completion of additional research assessments, and re‐contact about future research opportunities. All research data collected at the BHC will be made openly available to the scientific community through the BHC Research Database, encouraging collaborative and transparent research. The BHC actively involves public contributors with lived experience at all stages of the development and evolution of the service. Results: A six‐month pilot of 150 patients from a single memory clinic will launch in early 2020 to demonstrate feasibility and refine procedures, before expanding to other memory clinics. The pilot will incorporate evaluation of service‐user and clinician feedback and health economic measures. Conclusions: To prepare the UK health system for the future of dementia treatment and ultimately prevention, the BHC will provide a translational interface, enabling new advances in diagnosis, risk reduction and treatment to be rapidly implemented in clinical practice to provide better care for patients.